In-Silico Study of Bone Cancer Activity of N-Benzylideneaniline - Periyasamy, S.K.; Muralidharan, K.; Rajeshkannan, R. (Journal of Neonatal Surgery, 2025)
This study aims to describe the bone cancer activity of N-Benzylideneaniline , In this compound was predicted potential drug in medicinal field confirmed by swiss ADME software. Further, analaysed the bone cancer activity of N-Benzylideneaniline by Autodocking study and find out the binding energy compound. in this study was confirmed is very potential bone cancer drug. So, In future, N-Benzylideneaniline may be very effective bone cancer drug in the soceity and medicinal field.